2020
DOI: 10.1007/s40264-020-00955-y
|View full text |Cite
|
Sign up to set email alerts
|

A New Drug–Drug Interaction Between Hydroxychloroquine and Metformin? A Signal Detection Study

Abstract: Introduction Hydroxychloroquine was recently promoted in patients infected with COVID-19 infection. A recent experimental study has suggested an increased toxicity of hydroxychloroquine in association with metformin in mice. Objective The present study was undertaken to investigate the reality of this putative drug-drug interaction between hydroxychloroquine and metformin using pharmacovigilance data. Methods Using VigiBase ® , the WHO pharmacovigilance database, we performed a disproportionality analysis (cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It was shown that in northern Italy COVID-19 patients experienced significant elevated plasma concentrations of direct oral anti-coagulants while on medications used in the course of COVID-19 [ 10 ]. Unfortunately, with the exception of hydroxychloroquine and QTc-time prolongation due to co-administration of other drugs, the issue of potential harmful DDI in COVID-19 comorbid patients seems to be of minor attention with a limited number of published studies currently available [ [11] , [12] , [13] , [14] , [15] ]. Also, of a public health concern is the use of self-medication being potentially harmful or without evidence of clinical benefit taking place particularly in low- and middle-income countries with restricted access to quality healthcare and where drug dispensing is less controlled in the communities [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in northern Italy COVID-19 patients experienced significant elevated plasma concentrations of direct oral anti-coagulants while on medications used in the course of COVID-19 [ 10 ]. Unfortunately, with the exception of hydroxychloroquine and QTc-time prolongation due to co-administration of other drugs, the issue of potential harmful DDI in COVID-19 comorbid patients seems to be of minor attention with a limited number of published studies currently available [ [11] , [12] , [13] , [14] , [15] ]. Also, of a public health concern is the use of self-medication being potentially harmful or without evidence of clinical benefit taking place particularly in low- and middle-income countries with restricted access to quality healthcare and where drug dispensing is less controlled in the communities [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the incidence of heart failure was significantly lower in the metformin group compared to the non-metformin group (adjusted HR, 0.61; 95% CI, 0.43-0.87; p = 0.006) (19). An analysis of individual case safety reports of persons with Covid-19 on hydroxychloroquine suggested an increased risk of mortality associated with hydroxychloroquine + metformin use (ROR value of 57.7 (23.9-139.3) compared to hydroxychloroquine use alone (16). The authors found autophagosomes in mice treated with both, and hypothesized that the excess mortality was from a synergistic inhibition of autophagy (16).…”
Section: Safetymentioning
confidence: 99%
“…An analysis of individual case safety reports of persons with Covid-19 on hydroxychloroquine suggested an increased risk of mortality associated with hydroxychloroquine + metformin use (ROR value of 57.7 (23.9-139.3) compared to hydroxychloroquine use alone (16). The authors found autophagosomes in mice treated with both, and hypothesized that the excess mortality was from a synergistic inhibition of autophagy (16). Caution should be considered for co-administration in humans.…”
Section: Safetymentioning
confidence: 99%
“…Long-term clinical experience supported by numerous clinical studies clearly indicates that a substantial percentage of T2DM patients do not achieve the expected level of glycemic control while receiving metformin in monotherapy [ 278 ]. Considerable intra-individual variability in metformin response may be caused by numerous factors such as: age, gender, physical inactivity, insufficient dose of the drug, non-adherence, interaction between metformin and other drugs and metformin interaction with microbiota [ 279 , 280 ]. Experimental and clinical studies in both healthy volunteers and diabetic patients have shown that specific groups of genes (e.g., the family of SLC genes) are involved in metformin absorption, distribution, metabolism and elimination and, as a result, may affect the pharmacological response to this drug [ 281 , 282 , 283 , 284 , 285 ].…”
Section: Pharmacogenetics Of Metforminmentioning
confidence: 99%